The Impact of Work Stress and Job Burnout on Turnover Intention among Indonesia-China Integrated Industrial Employees - Yuliana, Lingga; Azmy, Ahmad; Nurwardana, Johan Ramadhan; Perkasa, Didin Hikmah; Alfian, Rendi; Aisah, Nur; Putra, Muhammad Farrel Risyawal (Journal of Applied Business Administration, 2025)
This research aims to analyze the impact of work stress and job burnout on Turnover Intention in companies located in the Indonesia-China Integrated Industrial Zone. A quantitative research method is used. Purposive sampling was a sampling technique involving 107 respondents. Data sources come from primary and secondary data. Primary data is distributed in the form of a questionnaire via Google Forms as an intermediary. Meanwhile, secondary data comes from internal case study companies. Closed statements were submitted in this study, and a Likert scale was used to indicate strongly disagree, disagree, agree, and strongly agree. Partial Least Square is a technique for data analysis using Smart PLS version 4.1.0.0 as a data processing tool. the first hypothesis indicates a relationship between work stress and turnover intention. Turnover intention and job burnout are unaffected by each other, as the second hypothesis demonstrates. Workers need to be able to handle a lot of work. This is due to work culture factors applied by Chinese migrant workers. Where workers are accustomed to uncertain work situations and work under pressure.